A Debate on the Islamic Practice of Pilgrimage to the Grave: Study of the Hadīth on Grave Pilgrimage for Women - Kamarudin Kamarudin; Sabil Mokodenseho (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This research aimed to analyze the hadīths and comments of 'ulamā' regarding the prohibition and permissibility of grave visitation by women. In the time of the Prophet Muhammad, the practice of visiting graves was strictly prohibited but later the prohibition was abolished. However, after the Prophet's death, the pros and cons surrounding the law on grave pilgrimage resulted in hostility, as the performers were accused of grave worship and convicted of heresy. Subsequently, the data were analyzed using the library research method with a comparative-compromising approach. The results showed that hadīths on the law of pilgrimage for women were not singular and had birthed several other laws. The admonishment of grave visitation by hadīths editors did not apply to all women because many supported pilgrimages, which made such curses nasākh. It denoted that hadīths prohibiting women from visiting graves were no longer valid, except for the 'illāt, which fulfilled the curse of women. Since different editorials will give rise to varying opinions regarding the grave pilgrimage for women, a compromise between hadīths is necessary to produce an accurate and accommodating legal formulation